Of Meat and Men: Sex Differences in Implicit and Explicit Attitudes Toward Meat - Love, Hamish J.; Sulikowski, Danielle (Frontiers in Psychology, 2018)
Modern attitudes to meat in both men and women reflect a strong meat-masculinity association. Sex differences in the relationship between meat and masculinity have not been previously explored. In the current study we used two IATs (implicit association tasks), a visual search task, and a questionnaire to measure implicit and explicit attitudes towards meat in men and women. Men exhibited stronger implicit associations between meat and healthiness than did women, but both sexes associated meat more strongly with 'healthy' than 'unhealthy' concepts, suggesting that the meat-masculinity association readily observed across western cultures may be mediated by a meat-strength/power association. The sex difference was not related to explicit attitudes to meat, nor was it attributable to a variety of other factors, such as a generally more positive disposition toward meat in men than women. Men also exhibited an attention bias toward meats, compared to non-meat foods, while females exhibited more caution when searching for non-meat foods, compared to meat. These biases were not related to implicit attitudes, but did tend to increase with increasing hunger levels. Potential ultimate explanations for these differences, including sex differences in bio-physiological needs and receptivity to social signals are discussed.